Experimental and theoretical investigation of tetra-oxidized terarylenes with high-contrast fluorescence switching1. (24th September 2015) - Kanazawa, Rui; Taguchi, Maki; Nakashima, Takuya; Kawai, Tsuyoshi
<x xml:space="preserve">Abstract</x> Photochromic tetra-oxidized terarylenes with ethyl-substituents at the reactive carbon atoms are demonstrated as turn-on fluorescent molecules.